Oryginalne ujęcie kwestii wiary w encyklice papieża Franciszka Lumen fidei - Henryk Sławiński (Polonia Sacra)
The article takes into consideration the encyclical letter of pope Francis Lumen fidei. The author discusses the description of the “faith” as found in the given pastoral letter. The original is not so much the matter of faith as such, but the description of faith from the biblical, patristical and existential point of view. That is why the role of the story in both receiving and in the transmission of the faith has been underlined, as well as the meaning of faith for the building of fraternal community of people of good will. What is quite original is the very deep connection between faith and love as well as the approach to the faith from the multidimensional, integrated perspectives of hearing, seeing and touching. One can find also in the pastoral letter Lumen fidei the invitation to discover the sings of God in one’s daily life.